Mechanical periodontal therapy in chronic periodontitis patients with postmenopausal osteoporosis using alendronate - (:unkn) unknown (Nova Science Publishers, Inc., 2013)
The objective of this chapter was to present the effect of mechanical periodontal treatment on clinical, microbiological and radiological parameters in chronic periodontitis patients with postmenopausal osteoporosis using oral alendronate. A total of 20 female patients were included. All of the patients were diagnosed as postmenopausal osteoporosis with a T score = -2.5 and defined to be in need of alendronate treatment by their gynecologists. The test group (n=10) consisted of patients who confirmed to undergo oral alendronate treatment whereas the control group (n=10) was made up with patients refusing any type of medication. Both of the groups received mechanical periodontal therapy. At baseline and 6 months after periodontal treatment, periodontal condition was assessed, subgingival microbial samples were evaluated by culturing, bone mineral density (BMD) of lumbar spine, femur and mandible was analysed by dual energy xray absorptiometry and mandibular cortical width (MCW) was measured by dental panoramic radiographs. Clinical evaluation revealed statistically significant periodontal improvements within both groups (p<0.01). Intergroup comparisons revealed a statistically significant difference for sulcus bleeding index only (p<0.05). The proportion of obligate anaerobes decreased significantly in both groups (p<0.05), however, no significant difference was found between the groups. While BMDs were decreased in the control group, significant increases were observed in the test group (p<0.01). Similarly, the MCW increased in the test group but decreased in the control group. Furthermore, a significant positive relationship was detected between the mandibular BMD and MCW (p<0.05). The results presented in this chapter suggest that oral alendronate therapy may have an adjunctive effect to mechanical periodontal treatment in terms of resolution of gingival inflammation in postmenopausal women with chronic periodontitis and osteoporosis. In addition, no side effect of orally administered alendronate was observed during this period. © 2013 Nova Science Publishers, Inc. All rights reserved.
Keywords: Alendronate; Bone density; Chronic periodontitis; Osteoporosis